Synthesis and structural and spectroscopic properties of a cyanido-bridged mixed-valence compound [Fe–NC–Ru–CN–Fe]. (20th March 2023) - Liu, Ming; Xiong, Yan; Xu, Weixiu; Wang, Yong
Abstract : Five cyanide-bridged compounds trans -[Cp(dppe)Fe(NC)Ru II (py)4 (CN)Fe(dppe)Cp][PF6 ] n and trans -[Cp(dppe)Fe(NC)Ru II (MeOpy)4 (CN)Fe(dppe)Cp][PF6 ] n were systematically synthesized and characterized. Abstract : The cyanide-bridged compounds trans -[Cp(dppe)Fe II (NC)Ru II (py)4 (CN)Fe II (dppe)Cp][PF6 ]2 (1, py = pyridine, dppe = bis (diphenylphosphino) ethane, Cp = cyclopentadienyl anion), trans -[Cp(dppe)Fe II (NC)Ru II (py)4 (CN)Fe II I (dppe)Cp][PF6 ]3 (2 ), trans -[Cp(dppe)Fe III (NC)Ru II (py)4 (CN)Fe III (dppe)Cp][PF6 ]4 (3 ), trans -[Cp(dppe)Fe II (NC)Ru II (MeOpy)4 (CN)Fe II (dppe)Cp][PF6 ]2 (4, MeOpy = 4-methoxypyridine) and trans -[Cp(dppe)Fe III (NC)Ru II (MeOpy)4 (CN)Fe II (dppe)Cp][PF6 ]3 (5 ) were systematically synthesized and characterized by IR spectroscopy, electronic absorption spectroscopy, elemental analysis, mass spectrometry and cyclic voltammetry. Fortunately, crystals of 1, 2, 4, trans -Ru II (MeOpy)4 (CN)2 and [CpFe III (dppe)Br](PF6 ) suitable for single-crystal X-ray diffraction analysis were obtained. The metal-to-metal charge transfer (MMCT) of the one-electron oxidation products 2 and 5 is mainly attributed to the Ru II and Fe II to Fe III MMCT transitions, and the MMCT of the two-electron oxidation product 3 is mainly attributed to the Ru II →Fe III MMCT transitions. According to the classification of Robin and Day, compounds 2, 3 and 5 belong to the class II mixed-valence compounds. The IR spectra, MMCT band and redox splitting of compounds 2 and 5 indicate that replacing the py ligand in the central unit with MeOpy shows better electronic communication properties.